2008
DOI: 10.1152/jn.00487.2007
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Cutaneous Stumble Correction When Tripping Is Part of the Locomotor Environment

Abstract: Haridas C, Zehr EP, Misiaszek JE. Adaptation of cutaneous stumble correction when tripping is part of the locomotor environment. J Neurophysiol 99: 2789 -2797, 2008. First published April 16, 2008 doi:10.1152/jn.00487.2007. We recently showed that cutaneous reflexes evoked by stimulating the superficial peroneal (SP; innervates foot dorsum) nerve are modulated according to the level of postural threat. Context-related modulation was observed mainly in contralateral (c) responses but not in the ipsilateral res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…Similar results can be obtained with mechanical perturbation of the swing phase (Dietz et al 1986;Schillings et al 2000). A perceived threat to stability has been shown to affect crossed reflex responses (Haridas et al 2005(Haridas et al , 2008. Thus in agreement with colleagues (2005, 2008) it is proposed that the currently described cBF activations reflect the facilitation of reflex pathways that are commonly recruited in cases of perceived instability (such as when ipsilateral perturbations threaten stability).…”
Section: Phase-dependent Increase In Cbf In Some Pd Patientssupporting
confidence: 83%
See 4 more Smart Citations
“…Similar results can be obtained with mechanical perturbation of the swing phase (Dietz et al 1986;Schillings et al 2000). A perceived threat to stability has been shown to affect crossed reflex responses (Haridas et al 2005(Haridas et al , 2008. Thus in agreement with colleagues (2005, 2008) it is proposed that the currently described cBF activations reflect the facilitation of reflex pathways that are commonly recruited in cases of perceived instability (such as when ipsilateral perturbations threaten stability).…”
Section: Phase-dependent Increase In Cbf In Some Pd Patientssupporting
confidence: 83%
“…Inversely, activation of the cortex through transcranial magnetic stimulation facilitates the reflex responses, indicating that there is convergence of the corticospinal tract and the reflex pathways involved in these responses, in confirmation of evidence obtained in cat studies (Bretzner and Drew 2005). These results prompted the suggestion that the cortical input may act to selectively change the gain in these reflex pathways (Haridas et al 2005(Haridas et al , 2008. It was found that conditions that posed a threat to stability during gait (such as walking with arms crossed when surface translations of the belt of the treadmill could occur) selectively increased the amplitude of responses in contralateral muscles (Haridas et al 2005).…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations